Investing in youth tobacco control: a review of smoking prevention and control strategies. Issue 1 (1st March 2000) - Lantz, Paula M; Jacobson, Peter D; Warner, Kenneth E; Wasserman, Jeffrey; Pollack, Harold A; Berson, Julie; Ahlstrom, Alexis
Abstract : OBJECTIVE: To provide a comprehensive review of interventions and policies aimed at reducing youth cigarette smoking in the United States, including strategies that have undergone evaluation and emerging innovations that have not yet been assessed for efficacy. DATA SOURCES: Medline literature searches, books, reports, electronic list servers, and interviews with tobacco control advocates. DATA SYNTHESIS: Interventions and policy approaches that have been assessed or evaluated were categorised using a typology with seven categories (school based, community interventions, mass media/public education, advertising restrictions, youth access restrictions, tobacco excise taxes, and direct restrictions on smoking). Novel and largely untested interventions were described using nine categories. CONCLUSIONS: Youth smoking prevention and control efforts have had mixed results. However, this review suggests a number of prevention strategies that are promising, especially if conducted in a coordinated way to take advantage of potential synergies across interventions. Several types of strategies warrant additional attention and evaluation, including aggressive media campaigns, teen smoking cessation programmes, social environment changes, community interventions, and increasing cigarette prices. A significant proportion of the resources obtained from the recent settlement between 46 US states and the tobacco industry should be devoted to expanding, improving and evaluating "youth centred" tobacco prevention and control activities.